2016
DOI: 10.3168/jds.2014-8428
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in dairy herds in the Netherlands from 2005 to 2012

Abstract: The aim of this study was to examine the variation in antibiotic use and the effects of external factors on trends in antibiotic use at the herd level by using the number of daily dosages as an indicator for antibiotic use. For this purpose, antibiotic use was analyzed in 94 dairy herds in the Netherlands from 2005 to 2012. The herds were divided into 3 groups of farmers: one group was guided in their antibiotic use from 2008 to 2010 as part of the project, whereas the other 2 groups were not actively guided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
147
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 30 publications
12
147
4
3
Order By: Relevance
“…Antimicrobial resistance (6, 7) and an increased risk of antibiotic residues in milk (8) are also associated with mastitis. Mastitis is the most common reason for applying antimicrobials to dairy cattle (9, 10). It therefore impairs the image of the dairy industry.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (6, 7) and an increased risk of antibiotic residues in milk (8) are also associated with mastitis. Mastitis is the most common reason for applying antimicrobials to dairy cattle (9, 10). It therefore impairs the image of the dairy industry.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cephalosporins in food producing animals is a controversial issue because they are a reserve antibiotic for human medicine. In this sense, many countries have implemented measures (directive 2003/99/EC) to restrict their use to a minimum to avoid resistances [1416]. …”
Section: Introductionmentioning
confidence: 99%
“…Dutch research in nearly 100 dairy herds over several years has reported that almost 70 per cent of animal-defined daily doses (ADDD) of antimicrobials were related to udder health, with 24 per cent of ADDDs for clinical mastitis alone (Kuipers and others 2016). …”
mentioning
confidence: 99%